Systemic Management of the Elderly with Purulent Inflammation in Oral Region - Hirose, Isao; Kin, Kensei; Hayashi, Naoki; Sato, Ken; Hirose, Yohsuke; Itoyama, Akira (Ronen Shika Igaku, 1996)
Purpose: Purulent inflammation can rapidly progress to severe conditions in elderly patients. Since extensive incision and drainage as a treatment for these conditions may cause intense pain and fear, general anesthesia is selected in some cases. The operation is performed under a general condition which rapidly deteriorates, and the depressed physical function with aging and complications including preoperatively existing systemic disease make intraoperative and postoperative management difficult. In this study, we examined problems concerning the intraoperative and postoperative management of elderly patients who were operated on under general anesthesia by incision and drainage. Subject and Methods: The subjects were 5 male and female patients aged from 72 years to 91 years who were operated on under general anesthesia by incision and drainage between October, 1984 and December 1994. Based on anesthesia records and medical records, the underlying medical diseases as complications, anesthesia, and intraoperative and postoperative management were examined. Results and Discussion: In all cases, underlying medical diseases and collagen diseases were observes as complications. Abnormal findings in preoperative clinical laboratory examinations were anemia, a decrease in TP, increases in BUN and creatinine levels, and hyperglycemia and abnormalities found on electrocardiograms. Long-term chronic administration of hypotensive drugs, oral hypoglycemic agents and adrenal steroid hormones was noted. Emergency operations were performed in 2 of 5 cases. In all cases, patients were anesthetized by slow anesthetization which had little influence on the cardiovascular system. Concerning intratracheal intubation, subconscious intratracheal intubation was performed due to trismus caused by inflammation in 3 cases. In some cases, a decrease in blood pressure, loss of consciousness and cyanosis occurred due to endotoxin shock, and intratracheal intubation was immediately performed in the ward. In other cases, administration of a low dose of sedative resulted in respiratory depression after entering the operating room, and intratracheal intubation was immediately performed. Anesthesia was maintained by gas oxygen and a low concentration of volatile inhalation anesthetic in 3 cases, and by a modified GO-NLA (gas oxygen-neuroleptanesthesia) method in the other 2 cases. For intraoperative management, dopamine was used to control the circulation for significant decreases in blood pressure in cases of endotoxin shock, and insulin therapy was required for diabetics. For postoperative management, respiratory care with a respirator was required because of delayed wakening and respiratory depression in some cases.Furthermore, tube feeding and correction of electrolytes were required for postoperative ingestion disorders and hyponatremia in other cases. Conclusion: These cases suggested that the procedure by incision and drainage for severe purulent inflammation in elderly people might frequently be performed when the patients general health is poor. Furthermore, respiration, circulation, metabolism and nutrition should be carefully controlled considering the impaired physical function with aging and underlyig medical diseases as complications in intraoperative and postoperative management.